Computation of Irregularity Indices of Certain Computer Networks. (17th August 2020) - Liu, Jiangnan; Cai, Lulu; Virk, Abaid ur Rehman; Akhtar, Waheed; Maitla, Shahzad Ahmed; Wei, Yang
Abstract : A graph is said to be a regular graph if all its vertices have the same degree; otherwise, it is irregular. In general, irregularity indices are used for computational analysis of nonregular graph topological composition. The creation of irregular indices is based on the conversion of a structural graph into a total count describing the irregularity of the molecular design on the map. It is important to be notified how unusual a molecular structure is in various situations and problems in structural science and chemistry. In this paper, we will compute irregularity indices of certain networks.